Analisis Kemampuan Technological Knowledge Calon Guru Sekolah Dasar - Hesti Fitriyana; Punaji Setyosari; Saida Ulfa (JKTP: Jurnal Kajian Teknologi Pendidikan, 2021)
Competent and professional teachers are important things that must exist for the realization of quality education. Technological Knowledge (TK) is part of the TPACK framework, which is the knowledge of teachers about technology that can support learning. This study aims to determine the ability of kindergarten elementary school teacher candidates for PGSD FIP UM students. This research uses the descriptive quantitative research method because it describes the ability of kindergarten teacher candidates using the analyzed numerical data. From the research that has been done, it can be seen that the knowledge of prospective teachers about types of software and technology is categorized as very good, the ability to teach students using web-based software is categorized as very good, the ability to use the software is categorized as good, the ability to use hardware is categorized as good. Based on the results of the study, it can be concluded that the ability of prospective elementary school teachers of PGSD FIP UM Kindergarten is included in the very good categoryAbstrakGuru yang kompeten dan professional merupakan hal penting yang harus ada demi terwujudnya pendidikan yang berkualitas. Technological Knowledge (TK) merupakan bagian dari kerangka TPACK merupakan pengetahuan guru tentang teknologi yang mampu menunjang pembelajaran. Penelitian ini bertujuan untuk mengetahui gambaran kemampuan TK calon guru sekolah dasar mahasiswa PGSD FIP UM. Penelitian ini menggunakan metode penelitian kuantitatif deskriptif karena mendeskripsikan kemampuan TK calon guru menggunakan data numerik yang dianalisis. Dari penelitian yang sudah dilakukan dapat diketahui bahwa pengetahuan calon guru tentang macam software dan teknologi dikategorikan sangat baik, kemampuan mengajar peserta didik menggunakan software berbasis web dikategorikan sangat baik, kemampuan menggunakan software dikategorikan baik, kemampuan menggunakan hardware dikategorikan baik. Berdasarkan hasil penelitian dapat disimpulkan bahwa kemampuan TK calon guru sekolah dasar PGSD FIP UM termasuk dalam kategori sangat baik.